Bike-share rebalancing strategies, patterns, and purpose. (July 2016) - Médard de Chardon, Cyrille; Caruso, Geoffrey; Thomas, Isabelle
Abstract: We provide a first spatio-temporal exploration of bicycle sharing system (BSS) rebalancing patterns from data extracted for individual stations at a fine temporal scale and operator interviews. Analyzing rebalancing operations for nine BSS, we describe implications for operators, municipalities, and future optimization work. We find that stations adjacent to transit hubs receive disproportionate amounts of rebalancing relative to trips and that rebalancing is more often responding to morning and afternoon demand exceeding station dock capacities rather than longer term accumulations of bicycles. More importantly, we observe some operator' rebalancing behaviors constrained between opposing goals of maximizing trips, profits, and service level agreements. Many BSS have no explicitly defined purpose, but existing rebalancing strategies can support or clash with the purpose or suggested benefits of a BSS. Graphical abstract: Highlights: Explores bike-share system (BSS) operator spatio-temporal rebalancing. Provides new metrics for system station characterization. Describes rebalancing operations of nine BSS. Service level agreement outages rates may decrease BSS efficiency. BSS purpose determines appropriate rebalancing strategy.